2021
DOI: 10.3390/ijerph18116085
|View full text |Cite
|
Sign up to set email alerts
|

Are There Differences in Video Gaming and Use of Social Media among Boys and Girls?—A Mixed Methods Approach

Abstract: Gaming is widespread among adolescents and has typically been viewed as an activity for boys. There are however a growing number of female gamers and we need to learn more about how gender affects gaming. The aim of this study is to both quantify gaming among Norwegian adolescents and explore how gender differences are perceived. A mixed method approach was used to capture gaming experiences among boys and girls. Survey data (N = 5607) was analyzed descriptively, and five focus groups were conducted, applying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(61 citation statements)
references
References 40 publications
6
52
0
3
Order By: Relevance
“…Prior studies support this phenomenon such that boys begin to identify themselves as gamers in early adolescence, when gender disparities typically increase. 29 , 30 Our findings extend known sex differences in time spent on screens to problematic screen use.…”
Section: Discussionsupporting
confidence: 72%
“…Prior studies support this phenomenon such that boys begin to identify themselves as gamers in early adolescence, when gender disparities typically increase. 29 , 30 Our findings extend known sex differences in time spent on screens to problematic screen use.…”
Section: Discussionsupporting
confidence: 72%
“…One analysis of a representative sample of Croatian students 9-17 years old showed that 70% of students play online video games at least once a week, while 40.3% of students played online video games almost every day (Ciboci et al, 2020). These data are comparable to those found in other countries, such as the Spain (e.g., , Norway (e.g., Leonhardt & Overå, 2021) and Italy (e.g., Donati et al, 2021).…”
Section: Introductionsupporting
confidence: 88%
“…The predominant social context for social network use or internet browsing was alone, whilst making phone calls/sending texts and playing electronic games was more likely to be done in the company of friends and/or siblings, though this varied by sex and day of the week. Numerous studies have reported that social networking and playing video games provide valued opportunities for young people to socialise with friends [ 35 ], but it is interesting to observe that this sometimes takes place alone and sometimes in the company of others. Any attempt to modify screen use in this population will need to account for the social function these activities hold in young peoples’ lives.…”
Section: Discussionmentioning
confidence: 99%